Komunikasi Digital dan Keterlibatan Politik: Menilai Pengaruh Platform Online terhadap Opini Publik - Roberta Maya Enjelia Lusi (CV. ULIL ALBAB CORP, 2024)
This research aims to evaluate the impact of digital communication through online platforms on political engagement and public opinion formation. Researchers will explore concepts such as social media influence, political participation theory, filter bubbles, and echo chambers to understand how the use of online platforms influences public opinion. Through a careful literature review study, researchers can develop a deeper understanding of the interactions between digital communication and political engagement and their impact on people's perceptions and attitudes in political contexts. The results found that the use of online platforms has a significant influence on public opinion in a political context. Social media, such as Twitter, Facebook, and Instagram, allow individuals to share information, views, and opinions widely and instantly. This research also makes an important contribution to understanding the role of online platforms in the democratization process and the dynamics of public opinion in the digital era.